Kritik, Kebebasan Berpendapat, dan Batas Hukum Ujaran Kebencian: (Studi Kasus Sengketa Verbal terhadap Shin Tae-yong) - Danang Kusuma Wardana; Ali Maskur (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the dynamics of public criticism of Shin Tae-yong's dismissal by PSSI as a phenomenon of digital communication that shows the tension between freedom of expression and the legal limits of hate speech. The background of this research stems from the intensity of netizens' reactions, which developed into collective moral pressure and had the potential to enter the realm of insults and hostility, as reflected in various comments, news reports, and verbal disputes involving public figures. This study aims to analyze how criticism, media framing, and netizen responses interact with the regulations of the ITE Law, particularly Article 28 paragraph (2), which is often used in reporting hate speech. The methods used are a normative juridical approach and case studies with document analysis, news reports, and academic literature techniques to identify patterns of digital expression and their legal relevance. The results of the study show that public criticism of Shin Tae-yong not only reflects performance evaluation, but also contains emotional, social identity, and moral dimensions that are reinforced by media framing and digital culture. The discussion confirms that the shift from criticism to hate speech occurs when public expression is not managed ethically, while law enforcement on hate speech articles still faces interpretation problems. In conclusion, this verbal dispute reflects the complexity of Indonesia's digital democracy and the urgency of legal reform